Alloy interface layer for solid sodium-ion battery and preparation method and application of alloy interface layer

By constructing a nano-scale metal Bi or Bi, Sn alloy interface layer on the surface of Na3Zr2Si2PO12 and forming a nano-Na-Bi alloy intermediate layer, the poor contact between Na3Zr2Si2PO12 and the Na metal negative electrode is solved, and the electrochemical performance and cyclic stability of solid-state sodium ion batteries are significantly improved.

CN119786751APending Publication Date: 2025-04-08ANHUI UNIV

Patent Information

Application Number
CN202411986550.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The poor contact between Na3Zr2Si2PO12 solid electrolyte and Na metal negative electrode leads to problems such as high interface impedance, poor interface stability, and sodium dendrite growth, which in turn affects battery life and efficiency.

Method used

The nano-scale metal Bi or Bi, Sn alloy interface layer is constructed on the surface of Na3Zr2Si2PO12 by vacuum thermal deposition, and a nano-Na-Bi alloy interlayer is formed in situ with the Na metal negative electrode.

Benefits of technology

The interface problem between Na3Zr2Si2PO12 and Na negative electrode was improved, the limit current density was improved, and stable circulation of 250 turns at 0.5C was 92.8%, and the Coulomb efficiency reached 99.95%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786751A_ABST
    Figure CN119786751A_ABST
Patent Text Reader

Abstract

The invention discloses an alloy interface layer for a solid-state sodium-ion battery and a preparation method and application of the alloy interface layer. By means of a vacuum thermal evaporation method, a nano Bi artificial interface layer is constructed on the surface of solid electrolyte Na3Zr2Si2PO12, the most appropriate film thickness is found through experimental comparison to serve as an intermediate layer precursor, and on the basis, a Na negative electrode directly covers a plating layer to generate a corresponding nano-scale Na-Bi alloy intermediate layer in situ. The method is easy and convenient to operate and wide in application, has very high universality, can freely control the film forming rate and thickness, is wide in material selection range, and provides a wider idea for subsequent Na3Zr2Si2PO12 negative electrode interface modification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid sodium battery and sodium ion solid electrolyte, and more specifically to an alloy interface layer for solid sodium ion battery and a preparation method and application thereof. Background Art

[0002] The demand for high energy density and environmentally friendly energy storage systems is growing in countries around the world. Lithium-ion batteries are currently the most mature energy storage batteries, but the scarcity of lithium resources leads to high costs for lithium-ion batteries, and traditional liquid electrolyte lithium-ion batteries also have safety issues, which affect the application of large-scale energy storage systems. Unlike lithium-ion batteries, sodium-ion batteries have the advantages of higher energy density and resource abundance, and the high safety brought by solid-state sodium batteries makes the research on sodium-ion solid electrolytes an important part of battery material research.

[0003] Na3Zr2Si2PO 12 Solid electrolytes have high ionic conductivity and excellent chemical / thermal stability, and are a major research target in the field of sodium ion solid electrolytes. 12 The solid electrolyte has poor contact with the Na metal anode, and there is no surface-modified Na3Zr2Si2PO 12 Solid electrolytes will have a series of problems during the battery charge and discharge cycle, such as high interface impedance, poor interface stability, and sodium dendrite growth, which will lead to reduced battery life and failure.

[0004] In response to the above problems, Xu Chaohe et al. disclosed a method for forming an interface in Na3Zr2Si2PO 12 Phosphorus is introduced into the sodium metal negative electrode of the solid electrolyte to form a Na3P composite negative electrode to improve the interface problem, significantly improve the interface wettability and reduce the interface impedance, and improve the serious expansion problem of the composite negative electrode (Xu Chaohe. A sodium-phosphorus composite negative electrode material, its preparation method and solid-state sodium battery: 202311300227.3[P]. 2024-01-02.), but there is still a problem of poor cycle stability; Mao Zhiyong et al. constructed an interface by ultrasonic welding, which has high strength, greatly reduces the interface impedance while maintaining interface stability, and has good cycle stability (Mao Zhiyong. All-solid-state alkali metal battery and its preparation method and application: 202110020566.0[P]. 2022-05-13.), but this method requires the solid electrolyte surface to be metallized in advance, and the overall process flow is relatively complicated.

[0005] Some techniques for solving interface problems have been reported in the current literature. For example, in the solid electrolyte Na3Zr2Si2PO 12The surface of the electrode is coated with a dispersion to form an interface layer to improve the contact between the electrolyte and the negative electrode, but the thickness and uniformity of the modified layer prepared by this method are difficult to accurately control, which may affect the stability of the electrode. In addition, there is also a method of using molten Na metal negative electrode to form a composite negative electrode to improve the interface contact, but there are problems such as complex preparation process, high processing difficulty and relatively short service life.

[0006] An alloy interface layer for solid-state sodium ion batteries and a preparation method and application thereof. Specifically, by means of vacuum evaporation, Na3Zr2Si2PO4 12 A nano-scale metal Bi or Bi, Sn alloy interface layer is constructed on the surface, and after further treatment, a nano-Na-Bi alloy intermediate layer is formed in situ with the Na metal negative electrode, solving the problem of Na3Zr2Si2PO 12 The above problems exist at the negative electrode interface. Summary of the invention

[0007] In view of this, the present invention provides an alloy interface layer for solid-state sodium ion batteries and a preparation method and application thereof. Specifically, by means of vacuum thermal evaporation, Na3Zr2Si2PO 12 A nanoscale metal Bi interface layer is constructed on the surface, and after further treatment, a nano Na-Bi alloy intermediate layer is formed in situ with the Na metal negative electrode, solving the problem of Na3Zr2Si2PO 12 The above problems exist at the negative electrode interface.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] A method for preparing an alloy interface layer for a solid-state sodium ion battery comprises the following steps:

[0010] (1) Na3Zr2Si2PO synthesized by solid phase method 12 Electrolyte tablets;

[0011] (2) Na3Zr2Si2PO 12 The electrolyte sheet is placed on a polishing machine and polished to a smooth and clean surface;

[0012] (3) Turn on the vacuum thermal evaporation apparatus, first place the prepared high-purity metal Bi particles at the evaporation source, and then 12 The electrolyte sheet is placed horizontally at the substrate;

[0013] (4) Select the evaporation material Bi and the final thickness in the evaporation apparatus program;

[0014] (5) Turn on the vacuum pump and wait until the vacuum degree reaches 1.0 to 1.5×10 -3 Pa, start to adjust the evaporation current;

[0015] (6) According to the standard evaporation current of Cu of the evaporator 125A, the true boiling point of Cu 2562°C, and the true boiling point of Bi 1560°C, select and input the starting evaporation current I1;

[0016] (7) Find the evaporation current suitable for Bi metal, increase the evaporation current by 2A every 5 minutes, and observe whether the Bi particles become molten;

[0017] (8) When the Bi particles become molten, the current at this time is recorded as I2, and the evaporation current continues to increase at the original rate;

[0018] (9) When the evaporation rate ≥ Stop increasing the current, observe the time-rate curve, and wait until the rate remains stable. Continue to increase the evaporation current until it stabilizes. range and the rate remains constant;

[0019] (10) Maintain the current unchanged, wait for the metal Bi evaporation to be completed, and then add Na3Zr2Si2PO 12 The electrolyte sheet was placed in the glove box for later use;

[0020] (11) Place the Na metal negative electrode on the Na3Zr2Si2PO 12 On the Bi-plated side of the electrolyte sheet, the coating gradually turns black, forming a Na3Bi alloy intermediate layer.

[0021] Preferably, the Na3Zr2Si2PO synthesized by the solid phase method in step (1) 12 The electrolyte sheet includes the following steps:

[0022] S1, weighing anhydrous sodium carbonate, zirconium dioxide, nano-silicon dioxide and ammonium dihydrogen phosphate, mixing and ball milling, and sintering the fully mixed powder to obtain a precursor powder;

[0023] S2. The precursor powder is ball-milled, dried, pressed into an embryonic body, and finally sintered to obtain the final Na3Zr2Si2PO 12 Electrolyte tablets.

[0024] Preferably, in step S1, the molar ratio of the sodium element in anhydrous sodium carbonate, the zirconium element in zirconium dioxide, the silicon element in silicon dioxide and the phosphorus element in diammonium phosphate is 3:2:2:1.

[0025] Preferably, in step S1, the ball milling is performed at a rotation speed of 300 rpm for 24 hours; and the sintering is performed by first keeping the temperature at 600° C. for 4 hours and then heating the temperature to 1150° C. for 4 hours.

[0026] Preferably, in step S2, the ball milling is performed at a rotation speed of 450 rpm for 2 hours; and the sintering is performed at 1200° C. for 6 hours.

[0027] Preferably, the polishing in step (2) is performed using sandpaper of 400 mesh or above.

[0028] Preferably, the final thickness in step (4) is

[0029] Preferably, the initial evaporation current in step (6) is 30-40A; and the I2 in step (8) is 70-75A.

[0030] Another object of the present invention is to provide an alloy interface layer for a solid-state sodium ion battery, which is prepared by the above-mentioned preparation method.

[0031] Another object of the present invention is to provide an application of the above-mentioned alloy interface layer for solid-state sodium ion batteries in solid-state sodium ion batteries.

[0032] Assembled NVP@C||Bi@NZSP||Na full battery, with a positive electrode active material loading of 1.4 mg / cm 2 The positive electrode material is composed of sodium vanadium phosphate, conductive carbon black and polyvinylidene fluoride in a mass ratio of 7:2:1, 1C = 117mA g -1 , the charge and discharge cycle was carried out at a rate of 0.5C, and a capacity retention rate of 92.8% and a coulombic efficiency of 99.95% were obtained after 250 cycles ( Figure 6 ).

[0033] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention uses a vacuum thermal evaporation method to deposit solid electrolyte Na3Zr2Si2PO 12 A layer of nano-Bi artificial interface layer is constructed on the surface, and the most suitable film thickness is found as the intermediate layer precursor through experimental comparison. On this basis, the Na negative electrode is directly covered on the coating to generate the corresponding nano-scale Na-Bi alloy intermediate layer in situ. This method is easy to operate, widely used, and has strong universality. It can freely control the film formation rate and thickness, and has a wide range of material selection, which is a good basis for the subsequent Na3Zr2Si2PO 12 Negative electrode interface modification provides a broader approach;

[0035] The present invention uses vacuum thermal evaporation technology to prepare Na3Zr2Si2PO 12 The nanoscale Na-Bi alloy intermediate layer on the electrolyte surface has good sodium affinity and can well improve the Na3Zr2Si2PO12 The interface problem between the negative electrode and Na. 12 , with the intermediate layer of Na3Zr2Si2PO 12 Able to have a higher limiting current density (0.5mA·cm -2 ), and can stably cycle 250 times at 0.5C rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0037] Figure 1 This is the X-ray diffraction pattern of 1μm thick metal Bi deposited on a glass plate.

[0038] Figure 2 Metal Bi is deposited on Na3Zr2Si2PO4 with a thickness of 1 μm 12 Scanning electron micrograph of the surface.

[0039] Figure 3 This is the X-ray diffraction pattern of the product obtained by in-situ generation of metal Bi with a thickness of 1 μm deposited on a glass plate and metal Na.

[0040] Figure 4 For the original Na3Zr2Si2PO 12 Sodium symmetric battery and 100nm coating modified Na3Zr2Si2PO 12 Comparison of interfacial impedance in electrochemical impedance spectroscopy of sodium symmetric batteries.

[0041] Figure 5 For the original Na3Zr2Si2PO 12 Sodium symmetric battery and 100nm coating modified Na3Zr2Si2PO 12 Comparison of limiting current densities of sodium symmetric batteries.

[0042] Figure 6 100nm coating modified Na3Zr2Si2PO 12 Capacity / Coulombic efficiency curve of the assembled full battery (positive electrode sodium vanadium phosphate, negative electrode metal Na) at constant current cycling at 0.5C rate (the inset is the charge and discharge curve).

[0043] Figure 7 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The technical solution of the present invention is further described below in conjunction with embodiments

[0046] Solid electrolyte Na3Zr2Si2PO 12 The preparation process is as follows: the solid electrolyte Na3Zr2Si2PO is synthesized by the traditional solid phase method. 12 . Weigh anhydrous sodium carbonate, zirconium dioxide, nano-silicon dioxide and diammonium phosphate, where the ratio of sodium in sodium carbonate, zirconium in zirconium dioxide, silicon in silicon dioxide and phosphorus in diammonium phosphate is 3:2:2:1. Ball mill at 300 rpm for 24 hours, keep the fully mixed powder at 600°C for 4 hours, and then sinter at 1150°C for 4 hours to obtain a precursor powder. Ball mill the precursor powder at 450 rpm for 2 hours. After drying, press it into a Φ12mm×1.5mm embryo, and finally sinter at 1200°C for 6 hours to obtain the final solid electrolyte sheet Na3Zr2Si2PO 12 .

[0047] Assembly of sodium symmetric battery: clean sodium foil is attached to Na3Zr2Si2PO 12 The two sides of the solid electrolyte sheet were placed in a swagelok and tightened to obtain sodium symmetric battery No. 1; clean sodium foil was attached to the 100nm coated Na3Zr2Si2PO 12 The two sides of the solid electrolyte sheet were placed in a swagelok and tightened to obtain a sodium symmetric battery No. 2. The sodium symmetric battery was used for comparative tests of electrochemical impedance spectroscopy and limiting current density (see Figure 4 and Figure 5 ).

[0048] Example 1

[0049] This embodiment provides a method for preparing an alloy interface layer for a solid-state sodium ion battery, comprising the following steps:

[0050] Step 1: Prepare the drugs and instruments required for the process (see Table 1 and Table 2 for details) and Na3Zr2Si2PO4 synthesized by solid phase method. 12 Solid electrolyte.

[0051] Step 2: Na3Zr2Si2PO12 The electrolyte sheet is placed on a polishing machine and polished with sandpaper of 400 mesh or above until it is smooth and the surface is cleaned until there is no dust or dirt.

[0052] Step 3: Turn on the vacuum thermal evaporation apparatus, first place the prepared high-purity metal Bi particles at the evaporation source, and then 12 The electrolyte sheet is placed horizontally at the substrate.

[0053] Step 4: Select the evaporation material "Bi" and the final thickness in the evaporation instrument program

[0054] Step 5: Turn on the vacuum pump and wait until the vacuum degree reaches 1.0~1.5×10 -3 Pa, you can start adjusting the evaporation current.

[0055] Step 6: According to the standard evaporation current of Cu of the evaporator 125A, the true boiling point of Cu 2562°C, and the boiling point of Bi 1560°C, select a relatively small starting evaporation current I1 and input it.

[0056] Step 7: Find the evaporation current suitable for Bi metal, increase the evaporation current by 2A every 5 minutes, and observe whether the Bi particles become molten.

[0057] Step 8: When the Bi particles become molten, the current at this time is recorded as I2, and the evaporation current continues to increase at the original rate.

[0058] Step 9: When the evaporation rate ≥ Stop increasing the current, observe the time-rate curve, wait until the rate remains stable, and continue to increase the evaporation current until the target

[0059] Step 10: Keep the current constant and wait for the metal Bi evaporation to be completed. Then, Na3Zr2Si2PO 12 The electrolyte sheet was placed in the glove box for later use.

[0060] Step 11: Attach the Na metal negative electrode to the Na3Zr2Si2PO 12 On the Bi-plated side of the electrolyte sheet, the coating gradually turns black, forming a Na3Bi alloy intermediate layer.

[0061] Table 1

[0062]

[0063] Table 2

[0064]

[0065] Example 2

[0066] The implementation steps are the same as those in Example 1, except that the thickness required in the fourth step is (i.e. 20 nm), other conditions remain unchanged, and the results obtained are close to those obtained in Example 1.

[0067] Example 3

[0068] The implementation steps are the same as those in Example 1, except that the thickness required in the fourth step is (i.e. 50nm), other conditions remain unchanged, and the results obtained are close to those obtained in Example 1.

[0069] Example 4

[0070] The implementation steps are the same as those in Example 1, except that the thickness required in the fourth step is (i.e. 200 nm), other conditions remain unchanged, and the results obtained are close to those obtained in Example 1.

[0071] Effect Experiment

[0072] Assemble symmetrical cells: Double-sided bismuth-deposited Na3Zr2Si2PO 12 The two sides were tightly attached with metal Na foil with a diameter of 9 mm, and then put into the swagelok and tightened. The electrochemical impedance spectroscopy and limiting current density tests were performed, and the result was 17.4Ω / cm 2 The specific interface impedance and 0.5mA / cm 2 The limiting current density.

[0073] Assembled full battery: positive electrode active material loading is 1.4 mg / cm 2 The positive electrode material is composed of sodium vanadium phosphate, conductive carbon black and polyvinylidene fluoride in a mass ratio of 7:2:1, 1C = 117mA g -1 , the charge and discharge cycle was carried out at a rate of 0.5C, and a capacity retention rate of 92.8% and a coulombic efficiency of 99.95% were obtained after 250 cycles ( Figure 6 ).

[0074] Figure 2 Metal Bi is deposited on Na3Zr2Si2PO4 with a thickness of 1 μm. 12 Scanning electron microscope image of the surface. The scale is 1μm, and the particle size is 200-300nm.

[0075] Figure 3 This is the X-ray diffraction pattern of the product generated in situ by metal Bi deposited on a glass plate with a thickness of 1 μm and metal Na, indicating that NaBi and Na3Bi compounds are generated by the coating reaction.

[0076] Figure 6 100nm coating modified Na3Zr2Si2PO12 The capacity / coulombic efficiency curve of the assembled full battery (sodium vanadium phosphate for the positive electrode and metal Na for the negative electrode) at a constant current cycle at a rate of 0.5C (the inset is the charge and discharge curve), with a positive electrode loading of 1.6mg. The full battery was stably cycled for 250 cycles at a rate of 0.5C, with a capacity retention rate of 92.8% and a coulombic efficiency of 99.95%.

[0077] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0078] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing an alloy interface layer for a solid-state sodium ion battery, characterized in that: The following steps are involved: (1) Na3Zr2Si2PO synthesized by solid phase method 12 Electrolyte tablets; (2) Na3Zr2Si2PO 12 The electrolyte sheet is placed on a polishing machine and polished to a smooth and clean surface; (3) Turn on the vacuum thermal evaporation apparatus, first place the prepared high-purity metal Bi particles at the evaporation source, and then 12 The electrolyte sheet is placed horizontally at the substrate; (4) Select the evaporation material Bi and the final thickness in the evaporation apparatus program; (5) Turn on the vacuum pump and wait until the vacuum degree reaches 1.0 to 1.5×10 -3 Pa, start to adjust the evaporation current; (6) According to the standard evaporation current of Cu of the evaporator 125A, the true boiling point of Cu 2562°C, and the true boiling point of Bi 1560°C, select and input the starting evaporation current I1; (7) Find the evaporation current suitable for Bi metal, increase the evaporation current by 2A every 5 minutes, and observe whether the Bi particles become molten; (8) When the Bi particles become molten, the current at this time is recorded as I2, and the evaporation current continues to increase at the original rate; (9) Stop increasing the current, observe the time-rate curve, and wait until the rate remains stable. Continue to increase the evaporation current until it stabilizes. range and the rate remains constant; (10) Maintain the current unchanged, wait for the metal Bi evaporation to be completed, and then add Na3Zr2Si2PO 12 The electrolyte sheet was placed in the glove box for later use; (11) Place the Na metal negative electrode on the Na3Zr2Si2PO 12 On the Bi-plated side of the electrolyte sheet, the coating gradually turns black, forming a Na3Bi alloy intermediate layer.

2. The method for preparing an alloy interface layer for a solid-state sodium ion battery according to claim 1, characterized in that: The Na3Zr2Si2PO4 synthesized by the solid phase method described in step (1) 12 The electrolyte sheet includes the following steps: S1, weighing anhydrous sodium carbonate, zirconium dioxide, nano-silicon dioxide and ammonium dihydrogen phosphate, mixing and ball milling, and sintering the fully mixed powder to obtain a precursor powder; S2. The precursor powder is ball-milled, dried, pressed into an embryonic body, and finally sintered to obtain the final Na3Zr2Si2PO 12 Electrolyte tablets.

3. The method for preparing an alloy interface layer for a solid-state sodium ion battery according to claim 2, characterized in that: In step S1, the molar ratio of the sodium element in anhydrous sodium carbonate, the zirconium element in zirconium dioxide, the silicon element in silicon dioxide, and the phosphorus element in diammonium phosphate is 3:2:2:

1.

4. The method for preparing an alloy interface layer for a solid-state sodium ion battery according to claim 2, characterized in that: In step S1, the ball milling is performed at a rotation speed of 300 rpm for 24 hours; the sintering is performed by first keeping the temperature at 600° C. for 4 hours and then heating the temperature to 1150° C. for 4 hours.

5. The method for preparing an alloy interface layer for a solid-state sodium ion battery according to claim 2, characterized in that: In step S2, the ball milling is performed at a rotation speed of 450 rpm for 2 hours; and the sintering is performed at 1200° C. for 6 hours.

6. The method for preparing an alloy interface layer for a solid-state sodium ion battery according to claim 2, characterized in that: The polishing in step (2) is performed using sandpaper of 400 mesh or above.

7. The method for preparing an alloy interface layer for a solid-state sodium ion battery according to claim 2, characterized in that: The final thickness in step (4) is 8. The method for preparing an alloy interface layer for a solid-state sodium ion battery according to claim 2, characterized in that: The initial evaporation current in step (6) is 30-40A; the I2 in step (8) is 70-75A.

9. An alloy interface layer for a solid-state sodium ion battery, characterized in that: Prepared by the preparation method according to any one of claims 2 to 8.

10. Use of the alloy interface layer for solid-state sodium ion batteries as claimed in claim 9 in solid-state sodium ion batteries.

Citation Information

Patent Citations

  • Solid electrolyte interface modification method and all-solid-state sodium battery

    CN115911525A

  • Sodium ion solid electrolyte, preparation method thereof and all-solid-state sodium ion battery

    CN119069774A

  • Method to Improve Sodium Electrochemical Interfaces of Sodium Ion-Conducting Ceramics

    US20230207787A1

Cited By

  • Alloy negative electrode composite sodium solid electrolyte material and preparation method and application thereof

    CN121662930A

  • Alloy negative electrode composite sodium solid electrolyte material, preparation method and application thereof

    CN121662930B